PENGEMBANGAN SISTEM INFORMASI ABSENSI KARYAWAN MENGGUNAKAN BARCODE PADA PT PRIMAYUDHA MANDIRIJAYA - Agung Tri Utomo; Suprihadi Suprihadi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
PT Primayudha Mandirijaya is one of the companies engaged in spinning cotton into yarn, the company has quite a lot of employees, in this case the need for proper attendance management, fast and accurate, this study discusses the design of a web attendance system using barcodes because in this case there is still attendance which is done manually will certainly be a hassle in filing employee data. The system is created using the PHP programming language using the MySQL database as a place to store employee data. The vue js framework is also used to enhance the appearance of the attendance system. barcode is one of the technology users that can make it easier to use. The system has been tested using UAT by obtaining 71.3% with a statement agreeing. Keywords— Barcode, Attendance, Vue js, Web, SDLC.